Carving a Space for Elite Republicanism: Hierarchy, Deference and Paternalism in American Political Development - O'Hara, Jonathan (Europolis, Journal Of Political Science And Theory, 2010)
The present article is a review of the American Political Development literature dealing with the issue of national administrative politics and development in late nineteenth century American history. Particular attention is paid to the ways in which historical institutionalists discount the importance of elite republican ideology as an explanation of national administrative growth. Attention is also paid to the ways in which sociological institutionalists view republicanism as a viable ideological alternative only for far flung and marginalized social interest groups. The article argues for studying the ideology also in terms of its elitist tradition and the tradition’s application to national administrative politics and development in the American context, emphasizing categories of hierarchy, deference and paternalism. As a review of seminal works related to the research program of American Political Development, this article is of particular use to those studying American development at the turn of the twentieth century.
Keywords: American politics; United States; dept.psc; elitism; ideology; republicanism

Calvin Coolidge - Hopper, Jennifer (Hatred of America's Presidents: Personal Attacks on the White House from Washington to Trump, 2018)
This work examines expressions of personal hostility and animosity toward presidents―even beloved ones―throughout American history and their impact on policymaking, politics, and culture.People involved or simply interested in politics often ask whether today's political environment is more toxic than ever before. Hatred of America's Presidents: Personal Attacks on the White House from Washington to Trump presents an impartial and authoritative history of invective toward the White House so readers can determine the answer for themselves.The book focuses on the most representative and commonplace attacks of a vitriolic and personal nature, detailing who instigated and trafficked in the attacks and how presidents, administrations, and political parties defended themselves. It also illustrates how honest disagreements about policy―such as FDR's New Deal, Ronald Reagan's Central America policies, George W. Bush's invasion of Iraq, and Barack Obama's Affordable Care Act―fueled expressions of hatred and condemnation. Finally, the book includes perspectives from both the right and the left on the legitimacy of these attacks and the victims' defenses as well as their impact on American politics and policy.
Keywords: dept.psc

James Buchanan - Hopper, Jennifer (Hatred of America's Presidents: Personal Attacks on the White House from Washington to Trump, 2018)
This work examines expressions of personal hostility and animosity toward presidents―even beloved ones―throughout American history and their impact on policymaking, politics, and culture.People involved or simply interested in politics often ask whether today's political environment is more toxic than ever before. Hatred of America's Presidents: Personal Attacks on the White House from Washington to Trump presents an impartial and authoritative history of invective toward the White House so readers can determine the answer for themselves.The book focuses on the most representative and commonplace attacks of a vitriolic and personal nature, detailing who instigated and trafficked in the attacks and how presidents, administrations, and political parties defended themselves. It also illustrates how honest disagreements about policy―such as FDR's New Deal, Ronald Reagan's Central America policies, George W. Bush's invasion of Iraq, and Barack Obama's Affordable Care Act―fueled expressions of hatred and condemnation. Finally, the book includes perspectives from both the right and the left on the legitimacy of these attacks and the victims' defenses as well as their impact on American politics and policy.
Keywords: dept.psc

Same-sex Marriage - Hooper, Jennifer (Encyclopedia of the American Presidency, 2017)
The most up-to-date reference of its kind, Encyclopedia of the American Presidency, Third Edition is the definitive guide to the role of the president from the American Revolution through the present day.
Google-Books-ID: 4EmJwwEACAAJ
Keywords: dept.psc

Campaign Finance - Hooper, Jennifer (Encyclopedia of the American Presidency, 2017)
The most up-to-date reference of its kind, Encyclopedia of the American Presidency, Third Edition is the definitive guide to the role of the president from the American Revolution through the present day.
Google-Books-ID: 4EmJwwEACAAJ
Keywords: dept.psc

War on Terror - Hooper, Jennifer (Encyclopedia of the American Presidency, 2017)
The most up-to-date reference of its kind, Encyclopedia of the American Presidency, Third Edition is the definitive guide to the role of the president from the American Revolution through the present day.
Google-Books-ID: 4EmJwwEACAAJ
Keywords: dept.psc

Affordable Care Act - Hooper, Jennifer (Encyclopedia of the American Presidency, 2017)
The most up-to-date reference of its kind, Encyclopedia of the American Presidency, Third Edition is the definitive guide to the role of the president from the American Revolution through the present day.
Google-Books-ID: 4EmJwwEACAAJ
Keywords: dept.psc

Diplomatic Amateurs or Qualified Professionals? Profiling the American Ambassador - Calin, Costel; Fitzpatrick, Kathy R. (White House Studies, 2013)
Are U.S. ambassadors qualified to lead America’s diplomatic missions abroad? This age-old question—often raised but seldom seriously considered by diplomacy scholars— is the focus of this study, which examined the professional credentials of American ambassadors appointed by former U.S. President George W. Bush. The article explores the relationship between the professional status of U.S. ambassadors and the power status and economic importance of host countries. The results showed that preferred destinations for amateur ambassadors were mostly Western European countries and countries with which the United States has large economic exchanges. Professional ambassadors were mostly appointed to African and Asian countries and to countries that have lower trade with the United States. The vast majority of semiprofessional diplomats were appointed to the most powerful countries.
Keywords: AMERICAN ambassadors; BUSH; George W. (George Walker); 1946-; DIPLOMATIC & consular service; GOVERNMENT missions; INTERNATIONAL relations; PRESIDENTS of the United States; dept.psc

The US PATRIOT Act (2001) - Buterbaugh, Kevin (Government at Work: Policymaking in the Twenty-First-Century Congress, 2016)
This edited volume features academic experts using leading policy frameworks to analyze the prominent U.S. public policy issues of the twenty-first century. Readers will learn about the similariti...
Keywords: dept.psc

Women Representatives in Britain, France, and the United States - Applewhite, Harriet Branson (Palgrave Macmillan, 2015)
"This book compares British, French, and American legislative debates on woman suffrage and women's rights. Beginning with an analysis of Tocqueville and J.S. Mill on the impact of suffrage, the book continues with analysis of floor debates, comparing gender style, the French on parity and the Americans on the ERA and concluding with modern debates"–
Keywords: France; Women; France; Women legislators; Great Britain; Women; Great Britain; Women legislators; History; Women; Suffrage; United States; United States; Women legislators; Women; dept.psc; faculty_collection

Professional Pathways to the Presidency - Marchant-Shapiro, Theresa (Palgrave Macmillan, 2015)
"During presidential elections a quadrennial debate emerges which, although it differs in the particulars, reflects the same structure in each reincarnation. Although the issue positions taken by the candidates vary over the years, their claim to qualification for the presidency follows a common pattern. Each candidate discusses his or her prior experience as preparation for one or more of the requirements of the office and then lays claim to the legacy of one of the great presidents who followed the same trajectory to the White House.Missing from this debate is a systematic analysis of how different job experiences prepared the population of all presidents for service. For each of the greats who followed a particular pathway to the presidents there is a failure who shared the pathway. In this book I combine the quantitative evaluation of presidential performance with mixture of qualitative and quantitative analyses of professional qualifications. The recent C-SPAN surveys provide us with a nuanced measure of presidential performance by asking historians to rate the Presidents on ten constituent attributes of: Public Persuasion, Moral Authority, Relations with Congress, Performance within Context of Times, Crisis Leadership, International Relations, Vision/Setting an Agenda, Economic Management, Administrative Skills, and Pursued Equal Justice for All. The sub-score for 'Relations with Congress' measures how well the president performs as 'legislator-in-chief' so that I can see whether former legislators work better with congress. Similarly the measure of 'Administrative Skills' indicates whether experience as a governor leads to better performance as the national chief executive. The evaluation of 'Economic Management' looks at whether those presidents with business experience do a better job in dealing with the economy. C-SPAN's nuanced measure of presidential performance allows a more careful evaluation of how prior experience affects particular aspects of presidential greatness than was previously possible"–, "Presidential hopefuls frequently claim they are qualified because their job experience is the same as a great president. However they ignore the failed presidents who shared the same pathway. This book evaluates all the presidents systematically to determine how prior professional experience influences presidential performance"–
Keywords: History; Vocational qualifications; Political aspects; Presidents; United States; dept.psc; faculty_collection

Statistics for Political Analysis: Understanding the Numbers - Marchant-Shapiro, Theresa (Sage CQ Press, 2014)
Keywords: Statistics; Textbooks; Textbooks; Political statistics; dept.psc; faculty_collection

A Post-Racial Change Is Gonna Come: Newark, Cory Booker, and the Transformation of Urban America - Wharton, Jonathan L. (Palgrave Macmillan, 2013)
Keywords: Booker; Cory; Metropolitan government; Case studies; Case studies; Mayors; Case studies; Newark (N.J.); Case studies; Post-racialism; Election; African American mayors; New Jersey; Newark; Newark; Urbanization; Political aspects; Politics and government; Newark (N.J.); Race relations; United States; dept.psc; faculty_collection

Lemkovyna: A History of the Lemko Region of the Carpathian Mountains in Central Europe - Polianskii, Ioann; Best, Paul J.; Decerbo, Michael; Maksimovich, Walter (Carpathian Institute, The Lemko Association, 2012)
Keywords: History; History; Carpathian Mountains; History; Lemkivshchyna (Poland and Slovakia); Lemky; dept.psc; faculty_collection

Abatement Addiction: A Case Study on Jersey City's Municipal Tax Abatements, Urban Gentrification and the Politics of Rights - Wharton, Jonathan (American Political Science Association, Social Science Research Network, 2011)
As New Jersey’s second largest city, Jersey City has experienced a surge in urban redevelopment and new development, particularly its downtown wards closest to New York City. Situated on the Hudson River directly across from downtown New York City, Jersey City is an ideal location for New Jersey developers and realtors to redevelop in order to attract New York City’s financial sector employees and individuals desiring more living space at lower rental or mortgage costs. In other words, downtown Jersey City exemplifies urban gentrification. In the last twenty years, several public policies helped spur waterfront development to attract potentially wealthier residents. In an effort to lure developers and investors, Jersey City officials relied heavily on municipal tax abatements to offset increasingly high property taxes. So after two decades, has Jersey City demonstrated that Payment in Lieu of Taxes (PILOT), tax abatements and other tax policy incentives are in fact feasible in terms of the following questions: What have been the implications of these policies? Who benefited from and who was marginalized from these policies? This paper examines the rising concerns surrounding tax abatements and other pro-development tax policies. By examining a medium sized city like Jersey City, this case study is especially useful in understanding the significant issues and shortcomings with urban redevelopment tax incentives. Too often these incentives benefit a political and financial elite at the economic expense and loss of political rights of long-term residents and renters.
Keywords: New Jersey; dept.psc; gentrification; tax abatements; urban development; urban politics; ⛔ No DOI found

A Post-Racial Change Is Gonna Come: Newark, Cory Booker, and the Transformation of Urban America - Wharton, J. (Springer, 2013)
This work offers a political and historical analysis of Newark's modern politics since 1950, culminating with Mayor Cory Booker's rise to power and prominence both in the city and in American political consciousness. Newark's recent political history offers an interesting case study in mayoral elections, community development, and coalition building politics. While Newark is the quintessential post-industrial city, Booker has received critical attention for his post-racial politics since he frequently bypasses racial and traditional urban politics. At the same time, relations between the mayor, the municipal council, and Newark's diverse communities were often so fractious that sustainable coalition building proved to be an elusive goal to resolve longstanding crime, education, and other social problems. Based on original interviews with Cory Booker, city council members, and other prominent Newark politicians, A Post Racial Change is Gonna Come is a powerful history of how Newark became the focal point for transformative politics in urban America.
Google-Books-ID: ZRZEAgAAQBAJ
Keywords: Political Science / General; Political Science / History & Theory; Political Science / Political Economy; Political Science / Public Affairs & Administration; Political Science / Public Policy / City Planning & Urban Development; Political Science / Public Policy / General; Political Science / World / European; Science / Earth Sciences / Geography; Social Science / Ethnic Studies / General; dept.psc

Unique Policymaking in Action: The District Council and the Legislative Process - Wharton, Jonathan L. (Law, Politics, and African Americans in Washington, DC, 2010)
Law, Politics, and African Americans in Washington, DC explores the legal challenges and triumphs of African Americans and law and politics in Washington, DC, a city whose majority population comprises African Americans. It examines the interconnection between law and politics in Washington, DC, because it is vital to know the legal conditions under which the African American residents of the most powerful city in the world live, based on sound empirical evidence. Law, Politics, and African Americans in Washington, DC addresses two major questions: - Why study African Americans in terms of law and politics? - Why examine law and politics at the local level, in this case Washington, DC?
Keywords: dept.pch

The Colonels' coup and the American embassy: A Diplomat's view of the breakdown of democracy in cold war Greece - Keeley, R.V.; Iatrides, J.O. (Penn State University Press, 2010)
The so-called Colonels' coup of April 21, 1967, was a major event in the history of the Cold War, ushering in a seven-year period of military rule in Greece. In the wake of the coup, some eight thousand people affiliated with the Communist Party were rounded up, and Greece became yet another country where the fear of Communism led the United States into alliance with a repressive right-wing authoritarian regime. In military coups in some other countries, it is known that the CIA and other agencies of the U.S. government played an active role in encouraging and facilitating the takeover. The Colonels' coup, however, came as a surprise to the United States (which was expecting a Generals' coup instead). Yet the U.S. government accepted it after the fact, despite internal disputes within policymaking circles about the wisdom of accommodating the upstart Papadopoulos regime. Among the dissenters was Robert Keeley, then serving in the U.S. Embassy in Greece. This is his insider's account of how U.S. policy was formulated, debated, and implemented during the critical years 1966 to 1969 in Greek-U.S. relations. © 2010 Robert V. Keeley All rights reserved.
Journal Abbreviation: The Colonels' Coup and the Amer. Embassy: A Diplomat's View of the Breakdown of Democr. in Cold War Greece Pages: 274 Publication Title: The Colonels' Coup and the Amer. Embassy: A Diplomat's View of the Breakdown of Democr. in Cold War Greece
Keywords: dept.psc

Disaster Response: EMDR and Family Systems Therapy under Communitywide Stress - Gelbach, R.A.; Davis, K.E.B. (Handbook of EMDR and Family Therapy Processes, 2012)
Journal Abbreviation: Handb. of EMDR and Fam. Ther. Proces.
Keywords: Communitywide stress; Disasters; Family systems therapy; Hyperarousal; Posttraumatic stress disorder; dept.psc

The United States and Greece in the twentieth century - Iatrides, J.O. (Greece in the Twentieth Century, 2013)
Journal Abbreviation: Greece in the Twentieth Century
Keywords: dept.psc

Presidential nominations in a Polarized Party System: The Republican primaries of 2012 - Paulson, A.C. (Winning the Presidency 2012, 2015)
Journal Abbreviation: Win. the Pres. 2012
Keywords: dept.psc

American Republicanism and the fin-de-siècle imperialism debate - O’Hara, Jonathan (Journal of Political Ideologies, 2014)
Aristotelian republicanism rests on an important premise, that persuasion is more virtuous than coercion. Nonetheless, there is an uneasy tension between the two approaches to rule in the republican tradition. This is particularly true with respect to Aristotle’s views on foreign policy, wherein coercive means of bringing about justice among nations may be viewed as much an offspring of republican thought as the exercise of moral suasion to the same end. This article takes this interesting tension in Aristotelian republican thought and attempts to apply it as an exegetical lens for looking into the republican ideological contours of the fin-de-siècle American imperialism debate. Particular attention is paid to how the tension in republican approaches to rule informed and helped give shape to the debate. Analysed through this lens is the rhetoric of two of the debate’s most important exponents, Theodore Roosevelt, advocating greater coercive means, and Carl Schurz, an advocate of moral suasion. © 2014 Taylor & Francis.
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00444 tex.type: [object Object]
Keywords: dept.psc; foreign policy; imperialism; morality; political ideology; social justice

Male versus female career ambassadors: is the US Foreign Service still biased? - Calin, Costel; Buterbaugh, Kevin (Foreign Policy Analysis, 2019)
This paper examines the appointment of male versus female career diplomats to ambassadorial posts. We assess the role played by ambassadors' individual characteristics, including education, marital status, and number of children, and host countries' characteristics, such as quality of life and regime type, in determining if a male or female is appointed to ambassadorial positions to represent the United States in foreign countries. The time frame of this study is the entire presidencies of Bill Clinton and George W. Bush (1993-2008), during which 603 career diplomats were appointed as ambassadors. The study provides empirical evidence that there remain significant differences between women and men serving as ambassadors. Female ambassadors are more likely to be single and have no children and are less likely to be Ivy League graduates than male ambassadors. Furthermore, they are more likely to be appointed to countries with lower quality of life and better human rights records. Finally, time plays a role in the likelihood of a woman being appointed as ambassador.
4 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000481423500004, lens.org/085-024-674-912-250 tex.address: [object Object] tex.affiliation: [object Object] tex.da: [object Object] tex.doc-delivery-number: [object Object] tex.eissn: [object Object] tex.journal-iso: [object Object] tex.keywords-plus: [object Object] tex.number-of-cited-references: [object Object] tex.publisher: [object Object] tex.research-areas: [object Object] tex.times-cited: [object Object] tex.type: [object Object] tex.unique-id: [object Object] tex.usage-count-last-180-days: [object Object] tex.usage-count-since-2013: [object Object] tex.web-of-science-categories: [object Object]
Keywords: dept.psc; peer-reviewed

Andrew Jackson - Marchant-Shapiro, Theresa (Hatred of America's Presidents: Personal Attacks on the White House from Washington to Trump, 2018)
This work examines expressions of personal hostility and animosity toward presidents―even beloved ones―throughout American history and their impact on policymaking, politics, and culture.• Investigates a unique form of expressions of hatred toward American presidents, focusing on the personal rather than the political• Covers every president from Washington to Trump• Includes coverage of personal attacks on First Families• Details how presidents and allies responded to these attacks
Keywords: dept.psc

Reexamining the Nineteenth-Century presidency and partisan press: The Case of President Grant and the Whiskey Ring Scandal - Hopper, Jennifer Rose (Social Science History, 2018)
Studies of the institutional development of the presidency and popular leadership by presidents over time lead us to contrary expectations as to how a nineteenth-century president would react to a major political scandal. Scholarship on newspapers of the late 1800s is also unclear on how a quasipartisan media, with some outlets moving toward independence, would cover a White House scandal. I find that a close analysis of the case of President Ulysses S. Grant and the Whiskey Ring scandal forces us to reconsider what we assume to be firmly modern developments in both presidential studies and media history. Though a supposedly “premodern” president, Grant still mounted a concerted effort to mitigate the damage of the scandal. Further, although the president could get his version of events across in prominent newspapers, Republican newspaper coverage was hardly reliable. Newspapers also connected politicians’ character and psychology to mistakes made in office and made presidential strategies to shape public perception clear to their audiences—emphases on political gamesmanship considered hallmarks of the modern media environment.
1 citations (Crossref) [2023-10-31]
Keywords: dept.psc; peer-reviewed

Local Mexico: Democratic Transitions in an Authoritarian Context - Olney, Patricia (FirstForumPress, a division of Lynne Rienner Publishers, Inc., 2018)
Keywords: Local government; Mexico; dept.psc; faculty_collection

Democracy in New England: a community politics reader - Wharton, Jonathan L. (Cognella Academic Publishing, 2018)
Keywords: New England; Politics and government; dept.psc; faculty_collection

Predicting revolt: Fragility indexes and the level of violence and instability in the Arab Spring - Buterbaugh, Kevin Neil; Calin, Costel; Marchant-Shapiro, Theresa (Terrorism and Political Violence, 2017)
This article is one of the first to systematically assess the ability of state fragility measures to predict violent protests and adverse regime changes in countries. We focus on the Arab Spring as an example of a situation that such measures ought to predict. Through a variety of analyses, we find that none of the measures are predictive. We then create a simple model using the literature of protest and revolts to predict both the level of violence and the extent of regime change in the Arab Spring countries. This simpler model does a better job of predicting the level of involvement in the Arab Spring than any of the complex State Fragility Indexes. Thus, the goal of this article is not to explain the causes of the Arab Spring, but to add to the discussion of the predictive value of measures of instability.
7 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000400285900008, lens.org/012-623-182-027-278 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Arab Awakening; Arab Spring; Arab awakening; Arab spring; Political violence; Protest; State Fragility Indexes; State fragility; State fragility indexes; dept.psc; political violence; protest; state fragility

Presidential Framing in the 21st Century News Media: The Politics of the Affordable Care Act - Hopper, Jennifer Rose (Routledge, 2017)
The Patient Protection and Affordable Care Act came into existence at a time when the president’s ability to lead the public was in question, political polarization had intensified, and the media environment appeared ever more fragmented, fast-moving, and resistant to control. Under such circumstances, how can contemporary American presidents such as Barack Obama build and maintain support for themselves and their policies, particularly as controversies arise? Using case studies of major contests over how key elements of the Affordable Care Act would be framed, and analysis of how those frames fared in influential and popular U.S. news sources, Hopper examines the conditions under which the president can effectively shape public debates today. She argues that despite the difficult political and communications context, the president retains substantial advantages in framing major controversial issues for the media and the public. These presidential framing advantages are conditional, however, and Hopper explores the factors that help make presidential frames more or less likely to gain hold in the news today. More so than in the past, an element of unpredictability in this news environment means that in pursuing favorable messaging, the president and his surrogates may also generate some unintentional consequences in how issues are portrayed to the public. Presidential frames can evolve with unfolding events to take on new meanings and applications, a process facilitated alternately by supporters, opponents, and media actors. Still, media figures and political opponents remain largely reactive to presidential communications, even as some seek to publicize and exploit weaknesses in the administration’s narratives. A close look at these recent cases casts new light on the scholarly debate surrounding the president’s ability to persuasively communicate and challenges conventional wisdom that the 21st century media largely present an unmanageable news environment for the White House. Presidential Framing in the 21st Century News Media engages with current events in American politics, focusing on the Obama Administration and the Affordable Care Act, while also reflecting upon the state of the American presidency, the news media, and the public in ways that have substantial implications for all of these actors, not merely in the present, but into the future, making it a compelling read for scholars of Political Science, Media Studies, Communication Studies, and Public Policy. © 2017 Taylor & Francis.
Keywords: Public opinion; United States. Patient Protection and Affordable Care Act; Health care reform; United States; Medical policy; United States; Medicare; dept.psc; faculty_collection

Greece and the birth of containment: An American perspective - Iatrides, John O. (The Balkans in the Cold War, 2017)
America’s strategy of containment, designed to confront postwar Soviet aggression, real and perceived, grew out of a series of disparate and seemingly unrelated conflicts. Thus the clash over the future of defeated Germany was direct, immediate and of obvious importance for vital United States interests in Europe and the world. By contrast, the communist insurgency in Greece was originally perceived as a basically domestic affair of a small country in a remote region of little strategic value. Yet the Truman Doctrine, which paved the way for containment’s gradual global implementation—Marshall Plan, Berlin airlift, NATO, wars in Korea and Indochina—was ostensibly focused primarily on Greece. After remaining a benevolent but deliberately passive observer of turmoil and violence in Greece, Washington boldly replaced Britain as the foreign patron of that small and troubled Balkan state. This study documents the transformation of United States policy toward Greece, and the birth of containment. It argues that the change was fundamentally one of perceptions of the nature of Soviet policy itself within the Truman administration, rather than of realities in Greece. In retrospect, Greece was an unlikely springboard for launching the strategy of containing Moscow’s ideology and power. The significance of the communist threat in Greece was more a matter of alarmist assumptions, loose perceptions and questionable symbolism than of hard facts and geostrategic realities. But in human affairs perceptions and symbolism are important, especially if clothed in an aura of success, as was the application of containment in Greece.
Citation Key Alias: lens.org/005-990-706-119-140
Keywords: American Official; Greek Government; Military Assistance; North Atlantic Treaty Organization; Security Interest; dept.psc